Heat resistance of Aspergillus sp. isolated from suman sa lihiya - Serrano, Jacqueline Diaz (2004)
ABSTRACT Fungi were isolated spoiled suman sa lihiya. The isolates were identified as two Aspergillus spp. and a yeast. Isolate B (Aspergillus sp.) was found to be the most heat resistant among the three fungi after heat treatment at 60°, 65°, 70°, and 75°C. Isolate A (Aspergillus sp.) and Isolate C (yeast) were inhibited at 70°C and 75°C respectively. The heat resistance characteristics of Aspergillus sp.spores were determined using the TDT tube method. Phosphate buffer was used as the suspending medium. Decimal reduction times of 1.17, 2.34, 9.88 and 32.0 minutes were obtained at 135°, 130°, 125° and 120° respectively. A corresponding z value of 10°F was derived from the regression line of the graph of the log10D-values versus temperature. A correlation coefficient of r^2 = 0.9834 for the TDT plot shows a good linear relationship of D-values versus heating te